Fecundity and gonado-somatic index of wild freshwater spiny eel Mastacembelus armatus (Lacepede) from Kishoreganj region of Bangladesh (Journal of the Bangladesh Agricultural University, 2014)
Fecundity and gonado-somatic index (GSI) of wild freshwater spiny eel Mastacembelus armatus were estimated from haor region of Kishoreganj district of Bangladesh. Estimated fecundity ranged from 2,235 to 19,493 for the fish measuring from 25 to 54 cm and weighing from 79 to 345 g. The minimum, median and maximum ova diameter was 0.20, 1.90 and 2.20 mm, respectively. The average numbers of ova present per g body weight were 45.41±8.85, 46.93±15.00 and 47.52±8.32 while the average numbers of ova present per g ovary were 369.64±40.66, 351.29±30.90 and 328.36±33.00 in the months of April, May and June, respectively. Maximum GSI for female spiny eel was 14.40±1.48 in the month of June and the minimum GSI for the same sex was 0.44±0.06 in September. The regression of fecundity on total length, body weight and gonad weight of female spiny eels were Log F = -0.875 + 2.957 × Log TL (r = 0.874), Log F = 0.630 + 1.461 × Log BW (r = 0.917) and Log F = 2.425 + 1.087 × Log GW (r = 0.977), respectively. Fecundity-gonad weight gave a better relationship when compared to fecundity-body weight and fecundity-total length relationship. DOI: http://dx.doi.org/10.3329/jbau.v11i2.19941 J. Bangladesh Agril. Univ. 11(2): 365-372, 2013